Sosialisasi Penggunaan E-Commerce Bukalapak Sebagai Pengembangan UMKM Di Desa Wadungasih - Ade Irmanistanti; Erick Kusuma Effendi; Mochammad Andi Prastyo; Yanuar Verga Moreno; Yudy Prasetyo; Mochammad Dicky Riza (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Nowadays, digital technology is in great demand because it offers easy access to a wide range of purposes and activities, including enabling innovation to generate business. The world of marketing will surely be heavily influenced by the advances of technology, the digital world, and the Internet. Marketing-based applications or e-commerce become the medium of sale and purchase transactions only but some have features as a program regulating the financial management of enterprises. Bukapalak can help UMKM perpetrators for media development, financial loyalties and new business opportunities. This dedication focuses on the perpetrators of the UMKM Village of Wadungasih, Kecamtan Buduran, Sidoarjo district. This dedication involves socialization activities with the stages of surveys, observations, and core activities. This dedication finds a lot of UMKM perpetrators who lack understanding of digital technology innovations as the times evolve. The purpose of this dedication is nothing more than a form of effort to develop and evaluate the progress of UMKM in an era of globalization where digital technology or e-commerce is used.